A Comparison of Instructional Methods on Clinical Reasoning in Entry-Level Physical Therapy Students: A Pilot Study. Issue 2 (15th June 2021) - Kobal, Kara L.; Rubertone, Patricia P.; Kelly, Stephanie Piper; Finley, Margaret
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The primary aim of this study was to provide a comparison of the effects of 2 commonly used pedagogical approaches (paper-based case studies vs authentic patient experiences) on clinical reasoning and critical thinking of second-year entry-level physical therapy students. Current literature reveals a lack of consistency in how clinical reasoning is taught and assessed in physical therapist education. There is a need for evidence-based approaches to develop clinical reasoning in entry-level physical therapy students in the United States. Subjects: Twenty-three students in their second year of a Doctor of Physical Therapy (DPT) degree program participated in this study. Methods: Participants were randomly assigned to a control group or to receive 1 of 2 supplemental learning activities (paper-based case studies or authentic patient experiences). Outcomes measured preintervention and postintervention included the Health Science Reasoning Test with Numeracy (HSRT-N) and the Self-Assessment of Clinical Reasoning and Reflection (SACRR). Data analysis included a comparison of effect sizes of change scores between groups and correlational analysis of pretest scores and student factors. Results: Authentic patient experiences demonstrated a moderate to large effect size for improved HSRT-N scores on 5 of 8 subscales, compared with paper-based case studies. Authentic patient experiences demonstrated a moderate effect size for improved SACRR scores compared with the control group. Discussion and Conclusion: The use of authentic patient experiences may be more effective than paper-based case studies for improving critical thinking and clinical reasoning in an entry-level DPT curriculum.